(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Vilfredo Pareto (1848-1923) once said: “For many events, roughly 80% of the effects come from 20% of the causes.”In this brief paper, I provide the well known AT Math to show why the Pareto Principle works.